Pengaruh Kinerja ESG, Struktur Modal Dan Return Saham Terhadap Nilai Perusahaan - Whita Ridlha Anjani; Zulfa Rosharlianti (CV. ITTC INDONESIA, 2026)
This study aims to empirically determine and demonstrate the influence of ESG Performance, Capital Structure, and Stock Returns on Firm Value. This study was conducted by analyzing companies across all sectors listed on the Indonesia Stock Exchange, which disclosed their ESG Performance scores according to Bloomberg for the 2019-2023 period. The population in this study was 649 companies, with a sample of 14 companies meeting the criteria. The analysis technique used purposive sampling. The data used in this study were secondary data in the form of financial reports from each company selected as a sample. This study utilized Eviews 13 software. The results showed that the best model was the Fixed Effect Model (FEM). This study shows that ESG Performance partially has no effect on Firm Value. Capital Structure variables do not affect firm value. Only stock returns have a significant effect. Meanwhile, this study shows that simultaneously, the ESG variables, Capital Structure and Stock Returns, have an 81% effect on Firm Value.